The spatial patterns of Korean investments and their effects on regional development in Indonesia until 1998 - R. Rijanta (Faculty of Geography, Universitas Gadjah Mada, 2005)
Korean investment in the ASEAN Region has grown tremendously during the last three decades, following the importance of Japanese investment in the same region. This is partly due to a favorable domestic growth in the Korean economy as stimulated by a successful agricultural reform and rural development on which industrialization takes place. Korea transformed itself from an underdeveloped, agricultural-based economy, into an industrialized country in Asia only within a very short span of time.This paper is aimed at assessing the spatial patterns and effects of Korean investment in Indonesian regional development before to the crisis. To achieve this general objective, an account on the general pattern of Korean investment is discussed from global level, Asia, ASEAN and Indonesia. Finally, an account for the spatial patterns and effects of Korean investment on regional development in Indonesia is presented.The paper is based on secondary data analysis. Data are gathered from various websites related to foreign investment in Indonesia as well as publications of various government organization for the spatial patterns and impacts of Korean investment. Data are analyzed using a simple descriptive statistics and thematic mapping.The research reveals that Korean investments in the world are mainly directed to USA, Europe and Southeast Asia. Southeast Asian Region has been the most important destination of Korean investment in the last three decades due to the availability of cheaper labor force, abundant natural resources, and favorable climate for investment and with little exception political stability. Recent investments are also directed to more capital intensive and more advance technology, thus facilitating the transfer of technology_ The distribution of Korean investment in Indonesia as any other foreign investments tends to be clustering in the surrounding areas of Jakarta, known as the Bogor, Tangerang; Bekasi (BOTABEK) Region where some 65 percent of foreign investment is located.. The effects of Korean investment on regional development at national level in Indonesia are very limited, but there is a substantial effect on the regional production structure, economic growth and employment generation at local-regional level, more especially in the main industrial agglomeration of the BOTABEK Region.